Effectiveness of Standard-Dose vs. Low-Dose Alteplase for Acute Ischemic Stroke Within 3–4.5 h - Chen, Chih-Hao; Tang, Sung-Chun; Chen, Yu-Wei; Chen, Chih-Hung; Tsai, Li-Kai; Sung, Sheng-Feng; Lin, Huey-Juan; Huang, Hung-Yu; Po, Helen L.; Sun, Yu; Chen, Po-Lin; Chan, Lung; et al. (Frontiers in Neurology, 2022)
Background: The efficacy and safety of intravenous alteplase administered 3–4.5 hours after acute ischemic stroke have been demonstrated. However, whether responses differ between low-dose and standard-dose alteplase during this time window and whether certain subgroups benefit more remain unknown. Patients and Methods: The current analysis was based on a multicenter matched-cohort study conducted in Taiwan. The treatment group comprised 378 patients receiving intravenous alteplase 3–4.5 hours after stroke onset, and the control group comprised 378 age- and sex-matched patients who did not receive alteplase treatment during the same period. Standard- and low-dose alteplase was administered to patients at the physician’s discretion. Results: Overall, patients receiving alteplase exhibited more favorable outcomes than did controls (34.0% vs. 22.7%; odds ratio [OR]: 1.75, 95% confidence interval [CI]: 1.27–1.42), and the effectiveness was consistent in all subgroups. Although patients in the standard-dose group (n = 182) were younger than those in the low-dose (n = 192) group, the proportions of patients with favorable outcomes (36.3% vs. 31.8%; OR: 1.22, 95% CI: 0.80–1.88) and symptomatic hemorrhage (2.8% vs 4.2%; OR: 0.65, 95% CI: 0.21–2.02) were consistently comparable in a covariate-adjusted model and an age-matched cohort. In the subgroup analysis, patients with cardioembolism, atrial fibrillation, and hypercholesterolemia were more likely to achieve favorable outcomes after receiving standard-dose than low-dose alteplase. Conclusion: In the 3–4.5-hour time window, the effectiveness and safety of standard-dose and low-dose alteplase may be comparable. A standard dose may be selected for patients with cardioembolism, atrial fibrillation, or hypercholesterolemia.